Federal reserve tools for managing rates and reserves - Antoine Martin; James McAndrews; Ali Palida; David Skeie (Federal Reserve Bank of New York, 2013)
Monetary policy measures taken by the Federal Reserve as a response to the 2007-09 financial crisis and subsequent economic conditions led to a large increase in the level of outstanding reserves. The Federal Open Market Committee (FOMC) has a range of tools to control short-term market rates in this situation. We study several of these tools, namely, interest on excess reserves (IOER), reverse repurchase agreements (RRPs), and the term deposit facility (TDF). We find that overnight RRPs (ON RRPs) may provide a better floor on rates than term RRPs because they are available to absorb daily liquidity shocks. Whether the TDF or RRPs best support equilibrium rates depends on the intensity of interbank monitoring costs versus balance sheet costs, respectively, that banks face. In our model, using the RRP and TDF concurrently may most effectively stabilize short-term rates close to the IOER rate when such costs are rapidly increasing.
Keywords: E42; E43; G12; G20; 330; monetary policy; fixed-rate full allocation overnight reverse repurchases; term deposit facility; interest on excess reserves; FOMC; banking